Human Capital Policies and the Distribution of Income: A Framework for Analysis and Literature Review - Daron Acemoglu (New Zealand Government, The Treasury, 2001)
Income and wage inequality increased rapidly in a number of OECD economies. This report surveys the literature on the determinants of wage and income inequality and presents a framework for analyzing policy. The focus is on human capital policies, but other policies that could also reduce income inequality are considered. The report concludes that increased income inequality in OECD economies reflects greater wage inequality and higher skill premia and that the most likely cause of the rise in skill premia is technical change that has increased the demand for skills and education, though changes in labor market institutions, such as minimum wage laws and the importance of union bargaining, are also likely to have played some role. Although increasing the supply of skills may have some beneficial effects, the most useful policies to reduce inequality would be those that can close the gap of skills between the top and the bottom of the income distribution, such as policies to improve the quality of secondary schooling and to encourage on-the-job training.
Keywords: 330